Leave the world behind [compact disc, unabridged] : a novel - Alam, Rumaan (Harper Audio, 2020)
Amanda and Clay head out to a remote corner of Long Island expecting a vacation: a quiet reprieve from life in New York City, quality time with their teenage son and daughter, and a taste of the good life in the luxurious home they've rented for the week. But a late-night knock on the door breaks the spell. Ruth and G.H. are an older couple, it's their house, and they've arrived in a panic. They bring the news that a sudden blackout has swept the city. But in this rural area, with the TV and internet now down, and no cell phone service, it's hard to know what to believe. Should Amanda and Clay trust this couple, and vice versa? What happened back in New York? Is the vacation home, isolated from civilization, a truly safe place for their families? And are they safe from one other?